2019
DOI: 10.1155/2019/1576359
|View full text |Cite
|
Sign up to set email alerts
|

Laser Therapy in the Treatment of Female Urinary Incontinence and Genitourinary Syndrome of Menopause: An Update

Abstract: Vaginal birth trauma is the leading cause of stress urinary incontinence (SUI) in women. Also, the process of ageing and hormonal deprivation in postmenopause alters the metabolism of connective tissues and decreases collagen production leading to pelvic floor dysfunction. Noninvasive treatment is recommended as first-line management of urinary incontinence (UI) in women. Surgical procedures are more likely to be implemented to cure UI but are associated with more adverse events. Sex hormone deficiency affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 49 publications
(58 reference statements)
0
33
0
4
Order By: Relevance
“…After reviewing the full‐text articles, an additional 20 records were excluded. This process resulted in 49 articles, 1,2,4,13‐58 which were further reviewed using a hand‐searching approach. Table 2 displays all the selected studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reviewing the full‐text articles, an additional 20 records were excluded. This process resulted in 49 articles, 1,2,4,13‐58 which were further reviewed using a hand‐searching approach. Table 2 displays all the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 displays all the selected studies. Of these, 37 were about the CO 2 laser, 1,2,4,13,14,17‐19,22‐27,29‐31,33‐37,39,42,45‐47,49‐58 10 were about the Erbium laser, 15,16,20,32,38,40,41,43,44,48 and two were about radiofrequency 21,28 . Outcomes of the studies included in the systematic review are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy-releasing systems developed for vulvovaginal use stimulate neocollagenesis and neoelastogenesis after the tissue surface temperature reaches 40-45°C [32]. Four decades of observation allows us to safely argue that there is no risk of neoplastic growth or DNA mutation.…”
Section: Energy-based Treatment For Gynecologic Conditions and Covid-19mentioning
confidence: 99%
“…Since 2015, many clinical studies have shown the advantages of different energy‐based devices (EBD) for the treatment of SUI/genitourinary syndrome of menopause (GSM), mainly Er:YAG and carbon dioxide (CO 2 ) laser [6]. Most studies have referred to the use of nonablative Er:YAG laser for the treatment of SUI [7–9], and one study specified its use for SUI and mixed urinary incontinence (MUI) [10].…”
Section: Introductionmentioning
confidence: 99%